Temporal dynamics of invertebrate and aquatic plant communities at three intermittent ponds in livestock grazed Patagonian wetlands. Issue 11 (26th March 2016) - Epele, Luis B.; Miserendino, María Laura
Abstract: Ponds are recognized worldwide as biodiversity hotspots; nevertheless in Patagonia studies are still needed that reveal the composition and status of their communities. This paper analyses the temporal patterns of aquatic invertebrates and assesses the environmental factors that best predict the variation in community structure at three small intermittent ponds, subjected to ranching practices (summer stocking) in the Patagonian steppe. Variables identified as important in structuring community assemblages were related to environmental conditions (rainfall and water temperature), chemical features (conductivity and pH) and biotic factors (macrophyte coverage). During the connected phase only a small number of invertebrate species were present, in contrast to the 11 taxa that were frequent and abundant during the isolated period ( Eucyclops chilensis, Hyalella curvispina and Rhionaeschna sp. were dominant). In this sequence the submersed Myriophyllum quitense and Lilaeopsis macloviana played a crucial role offering habitat and food resources. The present study provides valuable information that can contribute to minimizing the environmental damage and the development of strategies for the conservation of Patagonian wetlands.